Evaluation of public policies: Element of the evolution of practice and avenues of reflection for its institutionalization - BOUJRADI, Abdelkarim (Revue Internationale du Chercheur, 2025)
Since the beginning of the 1980s, public authorities have carried out continuous actions to anchor the evaluative practice in the Moroccan public landscape. The political commitment to the development of the evaluation practice is clearly reflected, whether at the level of the constitution of 2011, or at the level of the various orientations of the Head of State. However, despite this political will, the various actors struggle to integrate the evaluation of public policies into administrative practice. The objective of this research article is to study the evaluation of public policies from the perspective of its institutionalization. On the one hand, it examines the evolution of the practice of evaluation in the Moroccan public landscape, especially in its institutional dimension, while proposing its restructuring in three main phases. On the other hand, through the analysis of this evolution, this research hopes to develop avenues of reflection around the orientations likely to initiate a real process of institutionalization of the evaluation of public policies.